ЗАВДАННЯ ТА ФУНКЦІЇ СУДОВО-ЕКСПЕРТНИХ УСТАНОВ ТА ПРАВООХОРОННИХ ОРГАНІВ ЯК СУБ'ЄКТІВ ВЗАЄМОДІЇ - Полянський, Антон Олександрович (SUPREMANCE OF LAW, 2017)
The article analyzes the approaches of scientists to defi ning the tasks of the law enforcement system and law enforcement agencies in general. Attention is paid to the tasks assigned to the system of forensic institutions of our state. A scientific approach to the content and list of tasks of law enforcement agencies and forensic institutions as subjects of interaction has been formed. General approaches to the content and meaning of the function category are considered. The functions of forensic institutions and law enforcement agencies are analyzed. The list of functions of forensic institutions and law enforcement agencies as subjects of interaction is given.
Keywords: functions; tasks; functions of law enforcement agencies; tasks of forensic institutions; interaction; subjects of interaction